Subjective Testing and Objective Modelling of Influence of Different Social Classes to Voice Call Quality Perception - Holub, Jan; Soucek, Pavel (Communications - Scientific letters of the University of Zilina, 2012)
The paper presents the analysis of different perception of quality of transmitted voice by different social classes in conference call. Two different social classes (namely people with great income, who are older than 35 and people with low income, who are younger than 25) have been examined by means of ITU-T P.800 conversational tests. Significant differences in perception between those two classes have been identified.